2017
DOI: 10.1158/0008-5472.can-16-3566
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 in Cancer: Interactions and Vulnerabilities

Abstract: FOXM1 is a transcription factor of the Forkhead family that is required for cell proliferation of normal cells. However, FOXM1 is repeatedly overexpressed in a variety of human cancers and it has been implicated in all major hallmarks of cancer delineated by Hanahan and Weinberg. It has been postulated that the oncogenic potential of FOXM1 is determined by its capacity to trans-activate target genes that are implicated in different phases of cancer development. However, FOXM1 may also play an oncogenic role by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
145
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 30 publications
(62 reference statements)
5
145
1
2
Order By: Relevance
“…Well-differentiated epithelial-like cells have high CNI, whereas low CNI cells have abnormally-shaped nuclei ( Figure 1D). Consistent with the idea that low CNI is a marker of cancer progression and aggressiveness, this score was strongly and negatively associated with the mRNA levels of genes previously implicated in breast tumorigenesis including MCM4 35 , MCM10 36 , FOXM1 37 , CCNE2 38 , and MASTL 39 (Figure 1B). In addition, besides median I1 as an average measure, heterogeneity measures including standard deviation and skewness of morphology scores were also identified in this core network module;…”
Section: Hybrid Network Topological Analysis Revealed Tumour Morpholosupporting
confidence: 83%
“…Well-differentiated epithelial-like cells have high CNI, whereas low CNI cells have abnormally-shaped nuclei ( Figure 1D). Consistent with the idea that low CNI is a marker of cancer progression and aggressiveness, this score was strongly and negatively associated with the mRNA levels of genes previously implicated in breast tumorigenesis including MCM4 35 , MCM10 36 , FOXM1 37 , CCNE2 38 , and MASTL 39 (Figure 1B). In addition, besides median I1 as an average measure, heterogeneity measures including standard deviation and skewness of morphology scores were also identified in this core network module;…”
Section: Hybrid Network Topological Analysis Revealed Tumour Morpholosupporting
confidence: 83%
“…In addition, FOXM1 expression is a major predictor of poor outcome across a large set of cancer types [7]. This strongly supports the concept of FOXM1 as an actionable target for therapy [3,6] and encourages further exploration of FOXM1 function.…”
Section: Introductionsupporting
confidence: 59%
“…These proteins also play a pivotal role in the progression of cancers. The most important Forkhead Box (FOX) transcription factor involved in a multitude of pro-tumorigenic processes is FOXM1 [2,3]. The main gene regulatory activity of FOXM1 is attributed to cell cycle and mitotic control [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Many studies found that FoxM1 is a member of the Fox transcription factor family. 6 Many studies found that FoxM1 is a member of the Fox transcription factor family.…”
Section: Introductionmentioning
confidence: 99%